2007
DOI: 10.1210/en.2007-0289
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Derived Polyphenol Metabolite Enterolactone Is a Tissue-Specific Estrogen Receptor Activator

Abstract: Numerous dietary compounds can modify gene expression by binding to the members of the nuclear receptor superfamily of transcription factors. For example, dietary polyphenols, such as soy isoflavones genistein and daidzein, modulate the activity of the estrogen receptors (ERs)-alpha and ERbeta. An additional class of dietary polyphenols that modulate cellular signaling pathways are lignans, compounds that are common constituents of Western diets. In this study, we show that a metabolite of dietary lignans, ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
112
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 45 publications
4
112
2
2
Order By: Relevance
“…Among these, the estrogen receptors ERa and ERb have been shown to be activated by the mammalian lignans ENL and END [31,54]. We here found that ER expression is induced in epididymal fat by sesame and flaxseeds, suggesting that their effect on fat mass deposition might have been produced through a mechanism that involves an estradiol-mimicking action.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Among these, the estrogen receptors ERa and ERb have been shown to be activated by the mammalian lignans ENL and END [31,54]. We here found that ER expression is induced in epididymal fat by sesame and flaxseeds, suggesting that their effect on fat mass deposition might have been produced through a mechanism that involves an estradiol-mimicking action.…”
Section: Discussionmentioning
confidence: 51%
“…However, in light of the most recent progresses in the area of the study of natural ligands for the ERs from nutritional sources, the term ''phytoestrogen'' appears to be inadequate or poorly representative of the actual activity of the lignans, when considering metabolic functions as functional targets. The reason is that it is becoming frequent to observe that the same molecules that bind and activate the ERs, also bind and activate other NRs that may play opposite actions on the regulation of target genes (i.e., PPARc) and activate NR cross-talks with outcomes that are not clear [31,56,57]. An example of a lignan that binds the PPARs is macelignan [58,59], which has been determined as a dual ligand for PPARa/c receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, no changes were observed in ERa expression levels of E2-stimulated MCF-7 tumors in response to several weeks' of lariciresinol administration. Interestingly, the relative binding affinity of enterolactone to both ERa and ERb is very low, 25,49,50 suggesting that enterolignans do not act as classical ER agonists in breast tumors in vivo. However, in vitro and in vivo, enterolactone has been shown to induce estrogen responsive reporter gene expression in tissue specific manner through ERs, and to promote some estrogen responsive genes and morphological changes in estrogen target tissues (e.g., uterus) in female mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro and in vivo, enterolactone has been shown to induce estrogen responsive reporter gene expression in tissue specific manner through ERs, and to promote some estrogen responsive genes and morphological changes in estrogen target tissues (e.g., uterus) in female mice. 50 Thus, the ERa or ERb mediated effects of the dietary lignans and their metabolites acting systemically in normal endocrine target tissues cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%